A Study of Marketing Strategies of Electric Vehicles (EV) - Binti Mazlan, Nurul Nurfazlieqal; Binti Armi, Nurul Izzati Ain; Binti Ahmad Jais, Nurul Shafiqah Aida; Binti Mohamad Gani, Nurul Nadhirah; Jain, Vanshika; Poonia, Vandna; Rayhan, Rayhan (AIBPM Publisher, 2024)
The Electrical Vehicles (EV) industry is evolving in several ways. The technology behind EVs is improving, and so are the supporting facilities. At the same time, consumers have become more aware of electric vehicles as a viable option for their next vehicle purchase. In addition to these trends, fuel prices are ever-increasing while prices of EVs continue to fall. This means that more people can afford to drive an EV. The objective of this study is to know the marketing strategies of how electric vehicles can be used worldwide. This study applied descriptive quantitative method through survey which involved 100 Malaysian, Indonesian and Indian respondents. From the study, it can be found that satisfaction with electric vehicle’s efficiency, satisfaction with environmental friendliness, and public perception towards electric vehicle usage were variables that influence consumers’ behavior towards electric vehicles. Furthermore, satisfaction with being environmentally friendly has a strongest impact on consumer behavior above two other variables. It comes to conclusion that promoting electric vehicles as friendly environmental transportation to consumers can be the focus of marketing strategy in EV market.